Estudo dos elementos cis associados à resposta ao alagamento - Dias, Lara Isys (2011)
The current challenges in plant breeding are to maximize the productivity of major crop species and to create means for exploring novel crop environments. One of these environments is the lowland hydromorphic soils that are proper for the irrigated rice crop. Adapting other crops to this environment could reduce the incidence of diseases, pests and weeds, therefore benefiting from a crop rotation system. When a plant is exposed to abiotic stresses, it has to cope with environmental changes through physiological and anatomic changes that need quick gene expression responses, i.e., changes in active/silenced status as well as in the rates of transcription. Cis-acting regulatory elements have straight relationship with transcription factors (TF) in complex signaling networks. This TF binding sites (cis-elements) are the functional DNA elements that influence temporal and spatial transcriptional activity. We investigated possible patterns of sequences that can be inferred about the mechanisms that plants use to develop under flooding stress. This search for possible homologies between the various cis-elements would lead us to performed interactive analyses about how plants use their molecular mechanisms responding to abiotic stresses. Online databases were searched, looking for genes previously described in literature which are expressed in response to flooding in Oryza sativa, Arabidopsis thaliana and their homologous in Glycine max and Zea mays. The 1.0 Kb upstream portion of each gene was extracted and analyzed in silico. Besides, all the promoters of these four species were subjected to a tool for searching for novel signals, intending to find new motif patterns. Our in silico analysis shows that from 259 cis elements found in PLACE for all promoters of Arabidopsis and rice, 12 of them are common to both species, and are distinguished by having high frequency. Using the MEME program two consensus motifs could be found among the species Oryza sativa and Zea mays. These could represent new cis elements patterns, because they had relatively high occurrences in the gene promoters and they are related to conserved sequences in monocots. The analysis here presented shows important points for future studies related to the waterlogging stress and unmasking molecular tolerance mechanisms to this typical stress. From the data generated, it will be possible to direct experiments on genetic transformation with target genes and/or cis elements in order to attribute some characteristic in plants, such as those found in rice, so they can develop in an environment with O2 deprivation.